FEATURES OF THE COURSE OF PREGNANCY AND CHILDBIRTH AFTER IN VITRO FERTILIZATION (IVF), TAKING INTO ACCOUNT THE FACTOR OF INFERTILITY - Mirzayeva, D.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. One of the most popular ART methods is in vitro fertilization (IVF), which is the most effective method of infertility treatment. The study of the characteristics of pregnancy after IVF is of great practical importance, since only 55-70% of these pregnancies end in the birth of live children. Purpose. To study the features of the course of pregnancy in women after in vitro fertilization. Methods. The outcomes of pregnancy and childbirth were assessed in 155 patients after in vitro fertilization. The study was conducted in pregnant women after IVF, as well as 20 patients in the control group with spontaneous pregnancy. Results. The results of pregnancy and childbirth in 155 patients after in vitro fertilization were evaluated. The study was conducted in pregnant women after IVF. The course of pregnancy with IVF has been accompanied by obstetric complications, such as placental dysfunction, pre-eclampsia, fetal growth retardation syndrome, and premature birth. This has led to the need for a more differentiated approach to managing pregnancy after IVF. Conclusion. All women who have IVF treatment should be at high obstetric and perinatal risk and need more careful management of pregnancy and childbirth compared to women with spontaneous pregnancy.